[Gulf war, 1991 - Lazaro, Cheche (Quezon City Probe Productions, 1991)
Deals with a brief history of conflicts in the Arab countries, eruption of the 1991 war in the Persian Gulf and its effects to the Filipinos working there.
VHS.
Keywords: Persian Gulf War, 1991.; Filipinos -- Employment -- Saudi Arabia; Arab countries -- History